"A touch of physiotherapy" — the significance and meaning of touch in the practice of physiotherapy. (2nd January 2016) - Bjorbækmo, Wenche Schrøder; Mengshoel, Anne Marit
ABSTRACT: Touch, while ubiquitous and ever present in the practice of physiotherapy, is conspicuously absent from physiotherapy-related research. Based on a theoretical perspective inspired by phenomenology, this article explores and elaborates on the meaning and significance of touch in the practice of physiotherapy. The research data were generated through 16 close observations conducted in primary care clinics, and through interviews with 9 physiotherapists and with 9 patients suffering from chronic neck problems. The findings revealed how the use of touch in the practice of physiotherapy brings people into proximity in ways more complex than simple skin-to-skin contact. Through nontouch, touch, and movements, physiotherapists invite their patients to participate in the process of creating and performing therapy; dialogue through touch and movement is vital. Touch in physiotherapy depends on the physiotherapist's embodied skills; those they cultivate in order to respectfully listen to their patients and guide them to explore their own bodily capacity, limits and possibilities. The findings also suggest that observing therapy from outside and from participating in it offer significant different experiences, information, understanding, and meanings. The differences between physiotherapy as observed expression and as lived experience would seem to have important implications for understanding the practice of physiotherapy.